PENGEMBANGAN USAHA BUNGA ROSELLA DI KUOK KABUPATEN KAMPAR - Syafriani, Syafriani; Afiah, Afiah; Aprilla, Nia (COVIT (Community Service of Tambusai), 2021)
Rosella (Hibiscus sabdariffa L.) is a shrub or shrub which is a seasonal plant in the Malvaceae family. Rosella has many benefits. Roselle plant parts such as seeds, flower petals and leaves can be processed into a variety of foods. The purpose of this activity is to cultivate Rosella plants, to improve a product that is sourced from local wisdom which makes it a goal of this community empowerment activity to explore creative and innovative ideas, instill an entrepreneurial spirit, train mentally and teach hard work and responsibility not only to oneself. , but society. There are several obstacles encountered when carrying out activities, namely (1) limited capital. (2) the lack of Rosella flower plants in urban areas. (3) there is no diversity of processed Rosella flower products. (4) there is no diversity of processed Rosella flower products (5) the lack of people to cultivate Rosella flower plants. Activities that will be carried out in this PKM program include several development efforts, including syrup and candied rosella. The cost of profit from the sale of processed syrup products and candied rosella is sold at a price of Rp. 35,000 per bottle after calculating the making of betel leaf chips of Rp. 30,000, and then the sweets are sold at a price of Rp. 25,000 per pack after calculating the manufacture of betel leaf candy of Rp. 20,000. So that development efforts can increase the income of rosella farmer partners